2014
DOI: 10.3141/2457-11
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating Surface Microtexture in the Prediction of Skid Resistance of Flexible Pavements

Abstract: Monitoring and managing the skid resistance of the highway network is necessary for controlling and reducing the number of road accidents. High-speed measurements of surface texture can be used as a surrogate parameter for controlling a pavement's surface friction on the highway network. The two components of surface texture that affect skid resistance are the macrotexture and the microtexture. However, the technologies commonly used for measuring pavement texture at highway speeds account only for the macrote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(31 citation statements)
references
References 6 publications
0
27
0
4
Order By: Relevance
“…15 Several other descriptors exist to characterize the surface texture. For example, Serigos et al 16 describe the surface by means of using amplitude and slope parameters. The effect of the texture parameters on the skid resistance is analysed by using a linear regression model.…”
Section: Tyre/road Interaction -Existing Approachesmentioning
confidence: 99%
“…15 Several other descriptors exist to characterize the surface texture. For example, Serigos et al 16 describe the surface by means of using amplitude and slope parameters. The effect of the texture parameters on the skid resistance is analysed by using a linear regression model.…”
Section: Tyre/road Interaction -Existing Approachesmentioning
confidence: 99%
“…Both the macrotexture and the micro texture affect the relationship between vehicle speed and friction, and previous studies related texture depth and its variation to the variations in friction as a function of speed (2,7). Using stationary devices, Serigos et al demonstrated the improvement in the correla tion between friction and macrotexture when the pavement surface microtexture is characterized (8). The friction data collected with a BPT were correlated with macrotexture measured with the circular track meter and microtexture measured with a laser texture scanner (LTS).…”
Section: Monitoring Pavement Surface Macrotexture and Friction Case Studymentioning
confidence: 99%
“…This technology can create road surface laser data across an entire lane, measuring with high data precision, high data density, and measuring speed, and has been applied to measure rutting and cracks, even pavement quality assessment of smoothness and macrotexture [11][12][13][14][15]. Hao et al [16] used data interpolation and a surface fitting method to process a 10-point profile of 3D laser grooving data and calculated the depth to evaluate grooving abrasion status; the results were found to correlate well with the results of the sand patch method.…”
Section: Introductionmentioning
confidence: 99%